VD_FINDINFO HC / 2024 / 798 vom 17. Dezember 2024 - VD Tribunal cantonal (2024)
VENTE, RÉSOLUTION DU CONTRAT, CONTENU DU CONTRAT, RESTITUTIONEN GÉNÉRAL, PRIX | 1 CO, 107 CO, 108 CO, 109 CO, 184 CO, 19 al. 1 CO, 208 CO, 211 CO, 82 CO